Ethnicity, sex, FADS genetic variation, and hormonal contraceptive use influence delta-5- and delta-6-desaturase indices and plasma docosahexaenoic acid concentration in young Canadian adults: a cross-sectional study - Abdelmagid, Salma A; Clarke, Shannon E; Roke, Kaitlin; Nielsen, Daiva E; Badawi, Alaa; El-Sohemy, Ahmed; Mutch, David M; Ma, David WL (Nutrition & metabolism, 2015)
BACKGROUND: There is great interest in the relationship between polyunsaturated fatty acids and health. Yet, the combinatory effect of factors such as sex, ethnicity, genetic polymorphisms and hormonal contraceptives (HC) on the concentrations of these fatty acids is unknown. Therefore, we sought to determine the effects of FADS polymorphisms, and HC use in females, on aggregate desaturase indices (ADI), and plasma docosahexaenoic acid (DHA) concentrations in Caucasian and East Asian males and females. METHODS: Fasting plasma samples were collected from subjects (Caucasian males: 113 and females: 298; East Asian males: 98 and females: 277) from the Toronto Nutrigenomics and Health Study. Fatty acid concentrations were measured by gas chromatography. ADI were estimated by dividing concentrations of arachidonic acid by linoleic acid (n-6 ADI) and eicosapentaenoic acid (EPA) by α-linolenic acid (n-3 ADI). [DHA/EPA] desaturase index was used to determine effects of FADS2 polymorphisms and HC use on EPA conversion to DHA. RESULTS: In Caucasians, associations between n-6 ADI and multiple SNP (FADS1 rs174547, FADS2 rs174576, and rs174611 in males; FADS1 rs174547, FADS2 rs174570, rs174576, rs174679, rs174611, rs174593, rs174626, rs2072114, rs2845573, and rs2851682 in females) withstood multiple testing. In East Asian females, 5 SNP-n-6 ADI associations (FADS2 rs174602, rs174626, rs2072114, rs2845573, and rs2851682) withstood multiple testing. One FADS2 SNP was associated with altered [DHA/EPA] desaturase index in Caucasian females only (rs174576, p < 0.0001). HC use had a significant effect on DHA concentrations in Caucasian females only (P < 0.0001). CONCLUSIONS: We demonstrate ethnic- and sex-specific effects of FADS polymorphisms on desaturase indices, and ethnic-specific effect of HC use on plasma DHA concentrations.